055 Elevated blood pressure in offspring born to hypertensive pregnancy: is endothelial dysfunction the underlying vascular mechanism?. (22nd September 2015) - Lazdam, M; Pitcher, A; de la Horra, A; Kylintireas, I; Mannie, Z; Diesch, J; Trevitt, C; Singhal, A; Lucas, A; Neubauer, S; Alp, N; Kelly, B; et al.
Abstract : Background: Mothers with preeclampsia exhibit endothelial damage proportional to the severity of the condition. Higher blood pressure had been observed in their offspring and we hypothesised that this is a result of endothelial dysfunction also being present in the infant. This dysfunction should be greatest in those born premature due to severe preeclampsia and, as prematurity per se is associated with hypertension, we explored whether the underlying vascular phenotype differs from that observed when prematurity is not related to maternal vascular dysfunction. Methods: We studied 99 young adults aged 20–30. Seventy-one subjects were born preterm to a hypertensive (27%) or a normotensive pregnancy (73%), and 28 term controls born to uncomplicated pregnancies. Subjects underwent measurements of peripheral (BP) and central blood pressures (cBP). Endothelial dependent (FMD) and endothelial-independent brachial artery responses were assessed by ultrasound. Aortic stiffness was measured by pulse wave velocity (PWV) using applanation tonometry. Results: Offspring born premature either to hypertensive or normotensive pregnancy displayed significantly elevated peripheral (DBP 71.79±7.37, 71.61±6.52 vs 64.92±7.05, ANOVA p=0.0003 and MAP 87.93±7.61, 88.07±6.9 vs 81.62±8.06, ANOVA p=0.002) and central blood pressures (cSBP 115.96±10.86, 115.78±10.55 vs 96.71±9.86, ANOVA p<0.0001, cMAP 84.92±7.0, 84.13±8.9 vs 76.24±7.96, ANOVA p=0.0009 and cPPBP 46.56±8.63, 46.94±10.27 vs 30.71±4.82, ANOVA p<0.0001) compared to controls born at term. However, the offspring of hypertensive pregnancy had a distinct vascular phenotype with 40% lower FMD compared to subjects born at term to a normotensive pregnancy (4.25±4.02 vs7.27±5.12, p=0.035) and increased cIMT (0.52±0.04 vs 0.48±0.06, p=0.04). Whereas, those born premature to a normotensive pregnancy had normal endothelial responses but differences in PWV compared to term controls (5.92±0.84 vs 5.56±1.09, p=0.035). Conclusion: Prematurity is associated with elevated blood pressure in later life. In offspring of pregnancies complicated by preeclampsia or gestational hypertension, endothelial dysfunction is the predominant vascular phenotype. The findings direct attention towards endothelial dysfunction as a potential target for primary prevention in offspring of pre-eclampsia.